D-mannose-modified nanoliposomes enhance the targeted delivery of ovalbumin to improve its anti-inflammatory, antioxidant, and macrophage polarization effects - Jiahao Liao; Jianyu Huang; Xiaoyi Chi; Xiaoqiong Li; Jian Kuang; Jianqiang Li; Xiangyu Bian; Jinzhu Pang; Jinjun Li; Weiwei Wang (Journal of Functional Foods)
In this study, D-mannose-modified nanoliposomes (MLipo@OVA) were developed to facilitate the targeted delivery of ovalbumin (OVA) to macrophages. The subsequent anti-inflammatory, antioxidant, and macrophage-polarizing effects of OVA were investigated. The nanoliposomes were designed with DSPE-PEG and DPPC to enhance the bioavailability and stability of OVA. In vitro analysis showed that MLipo@OVA significantly increased macrophage uptake, with D-mannose further enhancing this effect. MLipo@OVA reduced pro-inflammatory cytokines (TNF-α, IL-1β) and increased anti-inflammatory IL-10 levels in LPS-induced macrophages, primarily via the inhibition of the TLR4/NF-κB pathway. Furthermore, ROS levels were decreased, SOD and GSH activity was enhanced, the Nrf2/HO-1 pathway was activated, and the compound exhibited strong antioxidant activity. MLipo@OVA also promoted M2 macrophage polarization by upregulating CD206 and Arg-1 and downregulating iNOS. Overall, these results indicate that MLipo@OVA could be used as a nanomedicine to facilitate targeted anti-inflammatory and antioxidant therapies.